Toward the massive genome of Proteus anguinus—illuminating longevity, regeneration, convergent evolution, and metabolic disorders. Issue 1 (3rd September 2021) - Kostanjšek, Rok; Diderichsen, Børge; Recknagel, Hans; Gunde‐Cimerman, Nina; Gostinčar, Cene; Fan, Guangyi; Kordiš, Dušan; Trontelj, Peter; Jiang, Hui; Bolund, Lars; Luo, Yonglun
Abstract: Deciphering the genetic code of organisms with unusual phenotypes can help answer fundamental biological questions and provide insight into mechanisms relevant to human biomedical research. The cave salamander Proteus anguinus (Urodela: Proteidae), also known as the olm, is an example of a species with unique morphological and physiological adaptations to its subterranean environment, including regenerative abilities, resistance to prolonged starvation, and a life span of more than 100 years. However, the structure and sequence of the olm genome is still largely unknown owing to its enormous size, estimated at nearly 50 gigabases. An international Proteus Genome Research Consortium has been formed to decipher the olm genome. This perspective provides the scientific and biomedical rationale for exploring the olm genome and outlines potential outcomes, challenges, and methodological approaches required to analyze and annotate the genome of this unique amphibian. Abstract : An international Proteus Genome Research Consortium has been formed to decipher the genome of Proteus anguinus (the olm). This perspective provides the scientific and biomedical rationale for exploring the olm genome and outlines potential outcomes, challenges, and methodological approaches required to analyze and annotate the genome of this unique amphibian.